2020
DOI: 10.7717/peerj.9194
|View full text |Cite
|
Sign up to set email alerts
|

A new species of freshwater crab of the genus Qianguimon Huang, 2018 (Decapoda: Brachyura: Potamidae) from Guangxi, Southern China

Abstract: A new species of freshwater crab of the genus Qianguimon Huang, 2018, is described from Guangxi Zhuang Autonomous Region, southern China. It can be distinguished from congeners by the following characters: male first gonopods bent inward at about 45° at base of terminal segment, carapace regions distinct and rugged and the female vulva opening inwards and downwards. In addition, molecular evidence derived from the 16S rRNA gene supported the species described in this study as a new species of Qianguimon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…2018a ). Despite this substantial diversity, the rate of discovery remains high ( Chu et al 2018b ; Huang et al 2018a , b , 2020a , b ; Naruse et al 2018 ; Zou et al 2018 ; Gao et al 2019 ; Wang et al 2019a , b , 2020a , b ; Mao and Huang 2020 ). With the two new species described in this study, Yunnan has a total of 18 genera and 67 species, highest among all provinces in China ( Chu et al 2018a ; Wang et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…2018a ). Despite this substantial diversity, the rate of discovery remains high ( Chu et al 2018b ; Huang et al 2018a , b , 2020a , b ; Naruse et al 2018 ; Zou et al 2018 ; Gao et al 2019 ; Wang et al 2019a , b , 2020a , b ; Mao and Huang 2020 ). With the two new species described in this study, Yunnan has a total of 18 genera and 67 species, highest among all provinces in China ( Chu et al 2018a ; Wang et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary analysis showed that this genus belongs to the "China-East Asia Islands" Group within the "Eastern-Asia Subclade" of the subfamily Potamiscinae (Shih et al 2009). Therefore, to confirm the phylogenetic position of the new genus and species, 24 additional 16S sequences from related genera from East Asia, Indochina and Southeast Asia in Shih et al (2009), Huang et al (2014Huang et al ( , 2017aHuang et al ( , b, 2018Huang et al ( , 2020d, and Wang et al (2019) were included for comparison. The variable regions in the loop regions of 16S that could not be aligned adequately for phylogenetic analysis were excluded (Shih et al 2009).…”
Section: Methodsmentioning
confidence: 99%
“…With 14 genera recorded to date (Bottapotamon Türkay & Dai, 1997, Chinapotamon Dai & Naiyanetr, 1994, Heterochelamon Türkay & Dai, 1997, Indochinamon Yeo & Ng, 2007, Lacunipotamon Dai, Song, He, Cao, Xu & Zhong, 1975, Longpotamon Shih, Huang & Ng, 2016, Mediapotamon Türkay & Dai, 1997, Neilupotamon Dai & Türkay, 1997, Potamiscus Alcock, 1909, Qianguimon Huang, 2018, Sinolapotamon Tai & Sung, 1975, Somanniathelphusa Bott, 1968, Tiwaripotamon Bott, 1970, and Yarepotamon Dai & Türkay, 1997, Guangxi Zhuang Autonomous Region is second, in China, only to Yunnan Province in the number of freshwater crab genera (Shih and Ng 2011;Huang 2018;Huang et al 2020d). From the number of new species described from this region in recent years (Zhu et al 2010;Naruse et al 2013;Do et al 2016;Ng 2017;Huang 2018;Zou et al 2018;Wang et al 2019Wang et al , 2020a, there is little doubt that many more remain to be discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater crabs are found in the tropics and subtropics in most parts of the world, occurring in aquatic habitats ranging from clear montane streams to lowland rivers and even in caves or tree holes ( Dai, 1999 ; Ng, Guinot & Davie, 2008 ). Southern China, where mountains and rivers are abundant, provides a multitude of habitats for a large number of species and the large numbers of new taxa reported in recent years indicate that research on this group remains in a “discovery” phase ( Yeo et al, 2008 ; Zhu, Naruse & Zhou, 2010 ; Naruse, Zhu & Zhou, 2013 ; Huang, Mao & Huang, 2014 ; Shih & Do, 2014 ; Huang, Shih & Mao, 2016 ; Huang, Shih & Ng, 2017 ; Huang, Ahyong & Shih, 2017 ; Ng, 2017 ; Huang, 2018 ; Huang, Shih & Ahyong, 2018 ; Huang, Wong & Ahyong, 2018 ; Wang, Huang & Zou, 2019 ; Wang, Zhou & Zou, 2019 ).…”
Section: Introductionmentioning
confidence: 99%